Continent, Coast, Ocean : Dynamics of Regionalism in Eastern Asia - Ding, Choo Ming; Ooi, Kee Beng (Book collections on Project MUSE., 2007)
Examines the dynamics of regionalism in Eastern Asia. Japan's diplomatic history as well as the heritage of its conquest of Eastern Asia is examined alongside China's cultural geography, paradigmatic dynamics, and intra-regional economics. Ties between East Asia and Southeast Asia, as well as the influence of American military power and European integration are also considered.